Pengaruh Gaya Kepemimpinan Delegatif, Beban Kerja, dan Kompensasi terhadap Turnover Intention Karyawan Pada PT. Medion Ardhika Bhakti Cabang Kediri - Bambang Suwarsono; Dimas Ulum` Maulana; Nuraidya Fajariyah (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
This study aims to determine the effect of delegative leadership style, workload, and compensation on employee turnover intention at pt. Medion ardhika bhakti branch of Kediri. The sampling technique in this study used a purposive sampling technique. The sample in the study was 40 people from PT. Medion Ardhika Bhakti Kediri Branch. Data obtained through questionnaires, observations, and interviews. The data measuring tool used is a Likert scale. The analysis technique of this research uses validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination (R2), and hypothesis testing. The results of the study show that the delegative leadership style variable does not have a partial significant effect on the turnover intention variable. Meanwhile, the workload variable has no partially significant effect on the turnover intention variable, and the compensation variable has a partially significant effect on the turnover intention variable. Delegative leadership style, workload, and compensation have a significant effect simultaneously on turnover intention variable